First-order phase transition and fate of false vacuum remnants. Issue 10 (1st October 2022) - Kawana, Kiyoharu; Lu, Philip; Xie, Ke-Pan
Abstract: False vacuum remnants in first-order phase transitions in the early Universe can form compact objects which may constitute dark matter. Such remnants form because particles develop large mass gaps between the two phases and become trapped in the old phase. We focus on remnants generated in a class of models with trapped dark sector particles, trace their development, and determine their ultimate fate. Depending on model and phase transition parameters, the evolutionary endpoint of these remnants can be primordial black holes, Fermi-balls, Q-balls, or thermal balls, and they all have the potential to constitute some portion or the whole of dark matter within a broad mass range. Notably, dark sector thermal balls can remain at high temperatures until the present day and are a new compact dark matter candidate which derives its energy from the thermal energy of internal particles instead of their mass or quantum pressure.